Explanation and Social Theory - Holmwood, John. author. aut Link
X, 244 p.
Keywords: Modern social science is largely pessimistic about social life and inquiry and this text traces the reasons for this. It argues for a creative and progressive social science to tackle the real problems of society and to find a solution which would expand human competence and practical resources.